Regulator of G-protein signaling 18 controls both platelet generation and function. - Nathalie Delesque-Touchard; Caroline Pendaries; Cécile Volle-Challier; Laurence Millet; Véronique Salel; Caroline Hervé; Anne-Marie Pflieger; Laurence Berthou-Soulie; Catherine Prades; Tania Sorg; Jean-Marc Herbert; Pierre Savi; et al. (PLoS ONE, 2014)
RGS18 is a myeloerythroid lineage-specific regulator of G-protein signaling, highly expressed in megakaryocytes (MKs) and platelets. In the present study, we describe the first generation of a RGS18 knockout mouse model (RGS18-/-). Interesting phenotypic differences between RGS18-/- and wild-type (WT) mice were identified, and show that RGS18 plays a significant role in both platelet generation and function. RGS18 deficiency produced a gain of function phenotype in platelets. In resting platelets, the level of CD62P expression was increased in RGS18-/- mice. This increase correlated with a higher level of plasmatic serotonin concentration. RGS18-/- platelets displayed a higher sensitivity to activation in vitro. RGS18 deficiency markedly increased thrombus formation in vivo. In addition, RGS18-/- mice presented a mild thrombocytopenia, accompanied with a marked deficit in MK number in the bone marrow. Analysis of MK maturation in vitro and in vivo revealed a defective megakaryopoiesis in RGS18-/- mice, with a lower bone marrow content of only the most committed MK precursors. Finally, RGS18 deficiency was correlated to a defect of platelet recovery in vivo under acute conditions of thrombocytopenia. Thus, we highlight a role for RGS18 in platelet generation and function, and provide additional insights into the physiology of RGS18.